An Ergonomic survey of Health Status of the Handloom Weavers - Durlov, Santu; Saha, Atanu; Mandi, Sasangbaha; Sahu, Subhashis (International Journal of Scientific Research in Biological Sciences, 2019)
Weaving is a one of the time honored crafts in the globe. The handloom industry is mainly a rural based cottage industry, where the processes are done mainly manually. Some handloom product of West Bengal like “Sari” (a traditional Indian dress worn by females in India) appreciated worldwide. It is an extensive piece of art work exclusively done manually by the weavers. The product development encompasses a wide range of tasks such as manual sorting of raw materials, dyeing, cutting, starching and adjustment of loom, arrangement of thread and spindle insertion, etc. This study was aimed at evaluating the different health problems and socio-economic conditions of the handloom weavers. Three hundred forty (340) weavers were randomly taken from different districts of West Bengal and 108 people from the same localities and similar socio-economic background were also taken as a referent. Detailed job profile of handloom weavers was also analyzed with the help of established standard questionnaire. It was observed that all types of weavers belong to low socio-economic condition and suffered from several health problems like pain in different body parts, eye constraint, respiratory problems and many more to say.